Perceptions on Adverbial Mobility in TESOL: A Survey of English Language Teachers in Port Harcourt, Nigeria - Ahaotu, Joseph Onyema (Colombian Applied Linguistics Journal, 2021)
This study examined the perceptions of teachers of English on adverbial mobility in order to determine how far it would be accurate to claim that adverbs are mobile. The researcher adopted the Lexical Approach, an alternative to traditional grammar-based foreign language teaching methodologies, as the framework for the study. The reliability of the study was demonstrated with a Cronbach’s alpha value of 0,83. The study approach was quasi-scientific, as the researcher administered a questionnaire on 50 respondents who are all English language teachers in Port Harcourt, Nigeria. The data obtained were analyzed using Spearman’s Rank Correlation Coefficient. The summary of the responses contrasts the more general perception of adverbs and adverbial groups as a highly mobile category that may be put in any sentential positions without altering meaning. Based on the opinion of a majority of the respondents in the study, the researcher concluded that they perceived adverbs as restrictively mobile and agreed that mobility presents challenges to their students’ use of adverbs. The study recommended, among other things, that teachers of English in TESOL contexts should incorporate the Lexical Approach in teaching adverbs and communication skills because the methodology enhances oral and written fluency as well as grammaticality.